2015
DOI: 10.1016/j.jbiotec.2015.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and highly efficient mammalian cell engineering via Cas9 protein transfection

Abstract: CRISPR-Cas9 systems provide a platform for high efficiency genome editing that are enabling innovative applications of mammalian cell engineering. However, the delivery of Cas9 and synthesis of guide RNA (gRNA) remain as steps that can limit overall efficiency and ease of use. Here we describe methods for rapid synthesis of gRNA and for delivery of Cas9 protein/gRNA ribonucleoprotein complexes (Cas9 RNPs) into a variety of mammalian cells through liposome-mediated transfection or electroporation. Using these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
540
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 627 publications
(561 citation statements)
references
References 20 publications
14
540
6
1
Order By: Relevance
“…To quantify the Cas9 expression level, we normalized the mean fluorescent intensity of the GFP + cells at each time point to that at 4 h. The Cas9 expression peaked at 24 h with 32.1% transfection efficiency (Figure 2A,B). Unlike our observation, previous work has shown that Cas9 was cumulatively expressed in HEK293T cells when using the plasmid‐loaded liposomal carrier 9. This suggests that this micellar approach may have lower off‐target effects on CRISPR/Cas9 editing due to its faster turnover rate.…”
Section: Resultscontrasting
confidence: 85%
“…To quantify the Cas9 expression level, we normalized the mean fluorescent intensity of the GFP + cells at each time point to that at 4 h. The Cas9 expression peaked at 24 h with 32.1% transfection efficiency (Figure 2A,B). Unlike our observation, previous work has shown that Cas9 was cumulatively expressed in HEK293T cells when using the plasmid‐loaded liposomal carrier 9. This suggests that this micellar approach may have lower off‐target effects on CRISPR/Cas9 editing due to its faster turnover rate.…”
Section: Resultscontrasting
confidence: 85%
“…The prophage-encoded inhibitor proteins AcrIIA2 and AcrIIA4, which allow phages to evade the bacterial host's CRISPR/Cas immune system, were found to inhibit Cas9-based targeting in their native host Listeria monocytogenes, as well as Cas9 of Streptococcus pyogenes in bacteria and human cells. Another approach for minimizing off-target effects employs the delivery of Cas9 protein/gRNA ribonucleoprotein complexes (37). When delivering Cas9 protein directly, cleavage occurs only temporarily, as the Cas9 protein is rapidly degraded in cells (38).…”
Section: Discussionmentioning
confidence: 99%
“…Two limitations for the use of the Cas9:sgRNA complex for genome editing are delivery into target cells and modification at off-target DNA sites (22)(23)(24). We and others have shown that delivery of the Cas9:sgRNA ribonucleoprotein complex results in comparable efficacy and reduced off-target cleavage events compared with traditional plasmid-based delivery methods (4,25). The ribonucleoprotein complex is anionic, facilitating complexation with cationic nanoparticles without the need for fusion with a supernegatively charged protein.…”
Section: Protein Charge Determines Gene Recombination Efficiencymentioning
confidence: 99%